Cultural diversity and the construction of the identity of the Iraqi university Vision analytical for the Iraqi situation - abad allah, Roaa luay (Al-Adab Journal, 2018)
The point of the study is the dialectical relationship between cultural diversity and building cultural unit . The point highlights the importance of the stage passed by the community at a time when there is a lot of cntrovevsy about the subject of cultural diversity and the possibility of building anation identity of university in which the interaction of all Iraqi cultures. The subject of research on the analysis of phenomena an knowledge of the changes affecting them in the local and regional context and what constitutes the globalization today of the external vaviable is affecting the structure of traditional societies the research proved that the Iraqi personality has continuous the research methodology was based on the method of inductive research to analyze the Iraqi cultural reality.